Significance of variables for discrimination: Applied to the search of organic ions in mass spectra measured on cometary particles. (25th January 2018) - Varmuza, Kurt; Filzmoser, Peter; Hoffmann, Irene; Walach, Jan; Cottin, Hervé; Fray, Nicolas; Briois, Christelle; Modica, Paola; Bardyn, Anaïs; Silén, Johan; Siljeström, Sandra; Stenzel, Oliver; et al.
Abstract: The instrument Cometary Secondary Ion Mass Analyzer (COSIMA) on board of the European Space Agency mission Rosetta to the comet 67P/Churyumov‐Gerasimenko is a secondary ion mass spectrometer with a time‐of‐flight mass analyzer. It collected near the comet several thousand particles, imaged them, and analyzed the elemental and chemical compositions of their surfaces. In this study, variables have been generated from the spectral data covering the mass ranges of potential C‐, H‐, N‐, and O‐containing ions. The variable importance in binary discriminations between spectra measured on cometary particles and those measured on the target background has been estimated by the univariate t test and the multivariate methods discriminant partial least squares, random forest, and a robust method based on the log ratios of all variable pairs. The results confirm the presence of organic substances in cometary matter—probably a complex macromolecular mixture. Abstract : The TOF‐SIMS instrument COSIMA (a secondary ion mass spectrometer with a time‐of‐flight mass analyzer) on board of the ESA mission Rosetta has collected dust particles in the neighborhood of comet 67P/Churyumov‐Gerasimenko, imaged them, and analyzed the elemental and chemical composition of the particle surfaces. This work evaluates a set of positive ion mass spectra with the aim to obtain information about ions consisting of C, H, N, and O atoms, originating from presumable organic material in the cometary particles. The data analysis methods applied are mostly from multivariate data analysis and estimate the importance of variables (which are related to ion masses and ion formulae) for a discrimination of spectra measured on cometary particles and on the background. The methods applied are t and u tests, discriminant partial least‐squares classification (D‐PLS), random forest classification, and a robust method based on pairwise log ratios of the variables (rPLS). Considering the results from complementary methods for estimating the variable importance gave a more complete picture than a single method. The origin of the secondary ions CH0‐3 +, C2 H0‐3 +, C3 H0‐4 +, and C4 + is shown to be the measured cometary material. These results—based on multivariate data evaluation—confirm the presence of organic matter in cometary particles, which is probably a complex mixture of macromolecular and unsaturated substances.